Uniaxial deformation of unfilled and filled joint - 174752 Haryati Awang (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Master of Civil Engineering(Geotchnics)) - Universiti Teknologi Malaysia, 2000